1999
DOI: 10.1017/s0033291798007806
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging differences between dementia with Lewy bodies and Alzheimer's disease: a pilot study

Abstract: Background. Temporal lobe atrophy on magnetic resonance imaging (MRI) has been suggested as a specific diagnostic marker for Alzheimer's disease (AD). No previous comparison with dementia with Lewy bodies (DLB) has been reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
1
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 24 publications
4
26
1
1
Order By: Relevance
“…However, the degree of GM reduction in the temporal region was much smaller in DLB than in AD (Fig 2). These results are in agreement with those of previous region-ofinterest [11][12][13] and recent VBM 18,19 studies. A greater loss of GM in AD could help explain the results of a neurophysiological study in which there was more severe episodic memory impairment in AD than in DLB.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…However, the degree of GM reduction in the temporal region was much smaller in DLB than in AD (Fig 2). These results are in agreement with those of previous region-ofinterest [11][12][13] and recent VBM 18,19 studies. A greater loss of GM in AD could help explain the results of a neurophysiological study in which there was more severe episodic memory impairment in AD than in DLB.…”
Section: Discussionsupporting
confidence: 94%
“…Volumetric studies have consistently shown a loss of GM in the MTLs, including the hippocampus and amygdala, in patients with DLB. 11,12 Although the regional patterns of cerebral GM atrophy in DLB overlap those of AD, the degree of GM loss in DLB is much lower than that in AD. 11,13 VBM was developed to assess the whole brain structure with a voxel-by-voxel comparison.…”
mentioning
confidence: 99%
“…By comparison, we found subjects with DLB demonstrated less atrophy of the hippocampus and parahippocampus. These results are in keeping with recent volumetric studies [5,6].…”
Section: Discussionsupporting
confidence: 93%
“…Recent volumetric studies [5][6][7] have indicated there may be less medial temporal lobe atrophy (MTA) on magnetic resonance imaging (MRI) in DLB compared with AD. However, it is not known whether differences are restricted to medial temporal lobe structures, or occur as part of a more diffuse pattern of temporal lobe atrophy involving lateral structures.…”
Section: Introductionmentioning
confidence: 99%
“…Our results, while in agreement with other reports of medial temporal lobe atrophy in AD [3,16], question the specificity of this finding regarding the other important subtypes of dementia. Using high resolution coronal MRI, we have recently shown that DLB is associated with less hippocampal atrophy than AD and VaD, which themselves showed a considerable degree of overlap [17,18]. In the current study, however, we did not find differences between DLB and other groups.…”
Section: Discussioncontrasting
confidence: 91%